The effect of the learning schedule strategy (K.W.L.H) on cognitive achievement and learning some futsal skills - Majeed Shwayyea, Hayder; Mhaibes Shatti, Wajdl (International Journal of Psychosocial Rehabilitation, 2020)
The research contained the introduction and its importance, and the researcher touched on the strategy of the learning schedule or what is called the self-table (KWL) which is one of the modern teaching methods and strategies as it seeks to achieve the demands of arousing students’ thinking and developing their tendencies and skills and providing them with the ability to search for solutions to the problems facing them which is one of the strategies Beyond knowledge that includes the mental processes practiced by the learner before, during, and after reading, which are concerned with thinking and his skills and aim to form the student and his knowledge of himself and allow him to involve all the senses in learning, which ultimately leads him to learn with meaning based on what the learner from previous information, to create a true And lasting concepts available, including. As for the research problem, it is embodied in the fact that there is an interest by most teachers and trainers in the education and training of basic skills and physical capabilities in general and the lack of focus on thinking and the use of modern strategies, including the learning agenda strategy during teaching and training skills in lessons and practical units that the student needs in skillful performances, which led the researchers to address this problem and develop appropriate solution proposals to address it. As for the fields of research, it included the human field that represents the fourth stage students and defines the temporal field for the period from (25/9/2019 to 8/12/2019), while the spatial field was in the sports hall of the Faculty of Physical Education and Sports Science at the University of Misan. The researchers used the experimental approach, and the research sampled of (24) female students of the fourth stage in the Faculty of Physical Education and Sports Science/ Misan University, distributed on two experimental and control groups, and by (12) students for each group, and the researchers used the skill tests for the special skills of a ball Lounges, as the SPSS system was used to obtain the results of the research, and the researchers concluded that there are significant differences in the results of special skill tests and cognitive achievement in football halls of the research sample, and the researchers recommended attention to the need to encourage the adoption of a learning schedule strategy (KWLH) in To teach because it enables students to employ their skills in guiding thinking and learning processes, and take personal responsibility in learning, based on the principle of self-learning.